Analysis of Clinicopathological Feature and Prognosis for Leptomeningeal Metastasis in Non-small Cell Lung Cancer - Min ZHU; Yanhong REN; Yan LIU; Chengjun BAN; Hua GU; Zheng WANG; Yuhui ZHANG (Chinese Journal of Lung Cancer, 2016)
Background and objective Leptomeningeal metastases (LM) is one of the most serious complications of advanced non-small cell lung cancer (NSCLC) due to the lower quality of life and poor prognosis. The aim of this study is to analyze the clinicopathological features and prognosis of patients with LM from NSCLC (NSCLC-LM). Methods Clinical data of 3 patients with NSCLC-LM collected from January 2015 to June 2016 were analyzed with a brief review. Results All 3 patients had adenocarcinoma histology harboring epidermal growth factor receptor (EGFR) exon 21 point mutations (m). Of the 3 cases, 1 was male, 2 were female. The mean age was 61.3 years (range, 59-64 years). The main clinical manifestations and positive physical examination included headache (3/3), dizziness (3/3), nausea (3/3) and vomiting (3/3), epilepsy (2/3), diplopia (1/3), hearing loss (1/3) and meningeal stimulation sign (3/3). The median time from symptom to diagnosis of LM was 2.3 months (range, 1 to 4 months). Except 1 patient with lung cancer and LM diagnosised at the same time, the other 2 cases received the diagnosis of LM after tyrosine kinase inhibitors (TKIs) therapy or chemotherapy respectively, the median time from diagnosis of NSCLC to LC was 8.5 months. The brain enhanced magnetic resonance imaging (MRI) manifestations of all 3 cases revealed linear meningeal enhancement. Cerebrospinal fluid in 3 cases were positive cytology in whom two cases had EGFR exon 21 L858R mutations, consistenting with the lung tissue. The symptom of the 2 cases improved after TKIs therapy, and temozolomide was used as supplement of 1 case of which the progression-free survival (PFS) and overall survival (OS) was 4.9 months and 13.9 months respectively. Conclusion Lung adenocarcinoma with sensitive EGFR mutations are likely to appear LM. Lacking of typical symptoms, NSCLC-LM was easily to be missed and misdiagnosed. TKIs therapy combined with temozolomide may be effective therapies for EGFRm-NSCLC-LM patients.